Some crude approximation, calibration and estimation procedures for NIG-variates - Jostein Lillestöl (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
In this paper we explore some crude approximation, calibration and estimation procedures for Normal Inverse Gaussian (NIG) variates of potential use in risk management. Among others we treat in some detail the calibration of bivariate NIG consistent with marginal NIG.
urn:nbn:de:kobv:11-10049614
Keywords: 330; risk management; Normal Inverse Gaussian distribution